Dogs Get Their Day At UPM - The Star, Vijenthi Nair Bailand (2008)
More than 600 dogs and their owners got together at Bukit Expo, Universiti Putra Malaysia (UPM), for a day out and made it into the Malaysia Book of Records as The Biggest Gathering of Dogs in Malaysia at the recent 12th Dogathon.